2023
DOI: 10.1183/16000617.0079-2023
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric events associated with montelukast in patients with asthma: a systematic review

Chris Wai Hang Lo,
Swathi Pathadka,
Simon Xiwen Qin
et al.

Abstract: Background:The United States Food and Drug Administration issued a black box warning on the mental health adverse effects of montelukast in 2020. Age-related effects on the risk of developing specific neuropsychiatric events in montelukast users remain largely unknown.Objective:To describe the risk of neuropsychiatric events associated with montelukast in adults and children with asthma.Methods:A systematic search of all studies investigating neuropsychiatric events in montelukast users was performed in PubMed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Ultimately, the results from our study demonstrated that pre-ICU exposure was greatly associated with the reduced incidence of delirium, suggesting a positive effect on the neuropsychiatric status of critically ill patients. However, it is important to note that MTK-related NAEs have been reported more frequently in children to date, possibly related to the fact that MTK is more commonly used in children, and possibly because children’s brains are at an early stage of maturation and the therapeutic effects of MTK are accompanied by a strong modulation of specific processes in the central system, resulting in a greater likelihood of adverse drug reactions [ 26 ]. Unfortunately, the MIMIC-IV database used in this study did not include data on ICU patients under 18 years of age, and only patients with a median age of 66 years were included, limiting the generalizability of the findings to the pediatric population.…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, the results from our study demonstrated that pre-ICU exposure was greatly associated with the reduced incidence of delirium, suggesting a positive effect on the neuropsychiatric status of critically ill patients. However, it is important to note that MTK-related NAEs have been reported more frequently in children to date, possibly related to the fact that MTK is more commonly used in children, and possibly because children’s brains are at an early stage of maturation and the therapeutic effects of MTK are accompanied by a strong modulation of specific processes in the central system, resulting in a greater likelihood of adverse drug reactions [ 26 ]. Unfortunately, the MIMIC-IV database used in this study did not include data on ICU patients under 18 years of age, and only patients with a median age of 66 years were included, limiting the generalizability of the findings to the pediatric population.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in a Danish nationwide health registry study of adults, montelukast was associated with increased neuropsychiatric events, albeit only in younger age groups (Jordan et al, 2023). And yet, a meta‐analysis of all studies examining neuropsychiatric events with montelukast found no association with suicide‐ and depression‐related events (Lo et al, 2023).…”
mentioning
confidence: 99%